Optical clearing for cancer diagnostics and monitoring - Oliveira, Luís (2022)
Cancer diseases are of major concern due to the lack of efficient early-stage diagnostic and effective therapeutic methods. Cancer detection is traditionally done at a later stage of development, using ionizing radiation. The pursuit of noninvasive optical methods for cancer detection has increased greatly in the past 30 years, but such methods may be ineffective if tumors are located in deep tissue layers, due to strong light scattering. The application of tissue clearing techniques brings new hope for the application of optical spectroscopy and imaging techniques for deep tumor detection. The combination of tissue clearing with optical imaging methods has demonstrated that higher resolution in deep tissue layers allows for better tumor detection than traditional ionizing methods. Due to the different protein content in normal and cancer tissues, the application of optical clearing procedures has already demonstrated that tumor diagnosis can be made through spectroscopic methods.